MacBook all-in-one for dummies - Chambers, Mark L. (John wiley & Sons, 2012)
Combining the fun-but-straightforward content of nine minibooks, this new edition of MacBook All-in-One For Dummies delivers helpful coverage of the rich features and essential tools you need to know to use the MacBook to its fullest potential. You'll learn an array of MacBook basics while veteran author Mark Chambers walks you through setting up your MacBook, running programs, finding files with Finder, searching with Spotlight, keeping track with Address Book, enjoying music with iTunes, creating cool multimedia projects with iLife, and more.